Implementasi Kebijakan Alokasi Dana Desa Di Desa Kotarindau Kecamatan Dolo Kabupaten Sigi - Nasrullah Nasrullah; Burhanuddin Soenoe (Jurnal ADMINISTRATOR, 2021)
The purpose of this study was to find out how to implement the Village Fund Allocation Policy (ADD) in Kotarindau Village, Dolo District, Sigi Regency. The basis of the research used in this study is qualitative research methods and the type of research using a qualitative descriptive approach. The informant withdrawal technique in this study was purposively by selecting the number of informants as many as 5 people who were considered to have knowledge about the implementation of the Village Fund Allocation (ADD) policy program in Kotarindau Village, Dolo District, Sigi Regency. Data collection techniques were carried out in two ways, namely library research and field studies consisting of observation, interviews and documentation. The method used in this research is using qualitative analysis methods. Based on the research results obtained by the researchers that from the aspects / dimensions of Communication, Disposition, and Bureaucratic Structure it has been going well. However, related to the aspect of resources, especially human resources, the results are still not good, so the authors conclude that the implementation of the Village Fund Allocation (ADD) program in Kotarindau Village, Dolo District, Sigi Regency is quite good. The supporting factors for the program are the establishment of good communication between program implementers and the target group, commitment and responsibility for implementing the program in accordance with community expectations